Enhancement of the Hydrogen Sorption on Mesoporous Carbon by Doping with Palladium Nanoparticles - Gerda, V.; Telbiz, G.; Kobylinskaya, N.; Zaitsev, V.; Manoryk, P.; Fraissard, J. (Хімія, фізика та технологія поверхні, 2010)
We have used the matrix synthesis protocol of Ryoo et al. for the preparation of highly ordered cubic mesoporous carbon (CMK-1) using mesoporous silica (MCM-48) as a template, in order to prepare palladium-doped CMK-1. The carbon obtained has a high surface area of 1800 m2g-1, a large porous volume of 1.14 cm3g-1 and average pore diameter of 3.03 nm. Step-by-step formation of mesoporous carbon was followed by X-ray diffraction, FTIR, N2 adsorption desorption and TPD mass-spectrometry. The physical data of CMK-1 are hardly changed by Pd incorporation (CMK-1/Pd). Transmission electron microscopy and Raman spectroscopy show that the framework of the highly ordered mesoporous carbon/Pd consists of an aligned carbon phase with a graphite mode region. The potential application of CMK-1 and CMK-1/Pd as sorbents for hydrogen storage is discussed.